Expression and Purification of the Thermus thermophilus Argonaute Protein - Daan Swarts; Matthijs Jore; John Oost (Bio-Protocol, 2014)
The Argonaute protein of Thermus thermophilus (TtAgo) has recently been studied in detail. For its in vitro characterization, TtAgo was purified after heterologous expression in Escherichia coli (E. coli). As TtAgo expression is toxic, a tightly controlled system was used for protein expression. The expression strain E. coli KRX carries a chromosomal T7 RNA polymerase gene under control of a rhamnose promoter. The ago gene is expressed via an IPTG-inducible T7 promoter. This allows for tightly (double) controlled expression of (toxic) TtAgo. Here, we describe the steps required for controlled expression and purification of this toxic protein.